The Feasibility of Assessing Teenagers' Oral English Language Performance with a Rubric - Diana Pineda (Universidad Nacional de Colombia, 2014)
This article reports the experience of a study group in a public university in Colombia, formed mostly by academic coordinators who worked in the design of assessment rubrics. Its focus is on the experience of the academic coordinator of the English program for teenagers, who concentrated on implementing the rubric to assess the students' oral performance. The data collection instruments used were the rubric and interviews with the teachers and students. The results are related to the impact of the assessment rubrics on the program's teachers regarding practicality.